1990
DOI: 10.1557/jmr.1990.0435
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-alkali-metal-graphite ternary intercalation compounds

Abstract: Alkali-metal-graphite intercalation compounds (alkali-metal-GIC's) absorb hydrogen in two ways: physisorption and chemisorption. Hydrogen uptake through the physisorption process occurs at low temperatures below about 200 K in higher stage alkali-metal-GIC's, where hydrogen molecules are stabilized to form a two-dimensional condensed phase in the galleries of the graphite sheets. The concentration of absorbed hydrogen molecules is saturated at a rate of H2/alkali metal atom ∼2. The hydrogen physisorption shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 87 publications
4
64
0
Order By: Relevance
“…The reported H2 isosteric heat on KC24 is 8.4 kJ mol -1 , about twice as large as for adsorption on bare graphite 87 . It is also known that the in-plane resistivity in KC24(H2)x is larger than in KC24 94 . This is explained by the observed c-axis expansion, which effectively reduces the in-plane carrier density.…”
Section: Properties Of Potassium-intercalated Graphitementioning
confidence: 97%
See 1 more Smart Citation
“…The reported H2 isosteric heat on KC24 is 8.4 kJ mol -1 , about twice as large as for adsorption on bare graphite 87 . It is also known that the in-plane resistivity in KC24(H2)x is larger than in KC24 94 . This is explained by the observed c-axis expansion, which effectively reduces the in-plane carrier density.…”
Section: Properties Of Potassium-intercalated Graphitementioning
confidence: 97%
“…They were explained in terms of a one-dimensional hindered diatomic rotor model 91,92 . By the late 1980's, a substantial body of research existed on hydrogen-alkali-metal graphite intercalation systems 93,94 . Interest in the area dwindled during the 1990's, as reflected in the small number of publications during the period.…”
Section: Constant Isosteric Heats and Intercalated Graphitesmentioning
confidence: 99%
“…It has been known that AGICs have catalytic activity for hydrogen and absorb hydrogen chemisorptively to form alkali metal hydride GICs through the dissociation of hydrogen molecules and charge transfer from AGICs to hydrogen [2,3]. The stage-1 graphite-potassium compound C 8 K, with a golden loster, is known to fix hydrogen and to become a dark blue compound C 8 KH 2/3 , which have the second stage structure [3,4]. The behaviors of hydrogen absorption and catalytic activities of AGICs have been known to depend on the structure, sort of metals and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Enoki et al [3] found out an interesting magnetic effect * This paper was presented at the 6th International Symposium on Surface Science -Towards Nano, Bio and Green Innovation-, Tower Hall Funabori, Tokyo, Japan, December 11-15, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The environment surrounding the H 2 sorption sites in KC 24 is impacted by a strongly polarized electric field between graphite layers, generated by charge transfer from potassium to graphite. 13,14 Overlapping graphite corrugation potentials from the host GIC structure are another significant feature. Hydrogen adsorption in KC 24 has an isosteric heat 9,10,15 of approximately −9 kJ mol −1 , in comparison to −4 kJ mol −1 for adsorption on graphite.…”
Section: Introductionmentioning
confidence: 99%